INTENSITAS SERANGAN HAMA BOLENG DAN HASIL UBI JALAR YANG DITANAM PADA BERBAGAI VARIASI KETINGGIAN MEDIA TANAM DALAM KARUNG: ATTACK INTENSITY OF SWEETPOTATO WEEVIL AND YIELD OF SWEETPOTATO GROWN AT VARIOUS GROWING MEDIA HEIGHT IN SACKS - Niyanti Esawati; Bambang Supeno; Ni Wayan Sri Suliartini (Universitas Khairun, 2026)
The sweet potato weevil (Cylas sp.) is the major pest of sweet potato and can cause tuber damage of up to 100%. This study aimed to determine the effect of different planting media heights in sacks on sweet potato weevil population, sweet potato weevil infestation intensity, and sweet potato yield. The research was conducted from October 2025 to January 2026 in a farmer-owned sweet potato field located in Sigerongan Village, Lingsar District, West Lombok Regency, West Nusa Tenggara, Indonesia. The experiment employed a Latin Square Design (LSD) consisting of five planting media height treatments (T1 = 20 cm, T2 = 30 cm, T3 = 40 cm, T4 = 50 cm, and T5 = 60 cm) with five replications. The observed parameters included identification of sweet potato weevil species, sweet potato weevil population, sweet potato weevil infestation intensity, sweet potato tuber weight, number of sweet potato tubers, sweet potato tuber length, and sweet potato tuber diameter. The identification results revealed the presence of two sweet potato weevil species, namely Cylas formicarius and Cylas puncticollis. Planting media height affected the sweet potato weevil population, with the highest population recorded at 20 cm (19 individuals) and the lowest at 60 cm (1 individual), but it did not significantly affect infestation intensity. The infestation intensity decreased from 15.23% (moderate category) at a planting media height of 20 cm to 1.67% (low category) at a planting media height of 60 cm. The 20 cm planting media height treatment produced the highest number of tubers, averaging 9.80 tubers per plant, while the 40 cm planting media height treatment resulted in the highest tuber weight, averaging 259.5 g per plant. Regression analysis showed a negative relationship between sweet potato weevil infestation intensity and sweet potato tuber weight (R² = 0.7416), as well as a positive relationship between sweet potato weevil population and infestation intensity (R² = 0.9449). Keywords: Cylas sp., sweet potato weevil, infestation intensity, planting media, sweet potato.